2003
DOI: 10.1053/ejvs.2002.1932
|View full text |Cite
|
Sign up to set email alerts
|

The retrojugular route: The ideal exposure for carotid endarterectomy performed under locoregional anesthesia

Abstract: The retrojugular route represents the ideal route for locoregional CEA; this exposure, with respect to the traditional approach, minimizes many of the disadvantages commonly considered as major deterrents of regional anesthesia for carotid surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 4 publications
2
13
0
Order By: Relevance
“…Awarenesso ft he potential for accessory nerve injury and knowledge of the mechanisms of injury should minimise risk. The few small studies published so far would also support the safety of the retrojugular technique 2,3,14 claiming it to be faster and to have asuperior exposure than the medial approach, particularly at the upper end of the internal carotid, with which we agree.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Awarenesso ft he potential for accessory nerve injury and knowledge of the mechanisms of injury should minimise risk. The few small studies published so far would also support the safety of the retrojugular technique 2,3,14 claiming it to be faster and to have asuperior exposure than the medial approach, particularly at the upper end of the internal carotid, with which we agree.…”
Section: Discussionsupporting
confidence: 65%
“…2,3 However, concerns have been raised with regard to cranial nerve injury witht he retrojugular approach, 4,5 in particular, whether the accessory nerve may be prone to injury.…”
mentioning
confidence: 99%
“…1,4,5,[7][8][9] The analysis included 740 CEAs, 333 of which were performed using the retrojugular approach and 407 with the antejugular approach. The reports were published between 2002 and 2009.…”
Section: Resultsmentioning
confidence: 99%
“…Significant heterogeneity in study design was identified. Two studies were randomised controlled trials (RCTs) 5,6 and another three studies were retrospective or prospective observational reports. 1,4,9 A correspondence reporting a brief summary of a single author retrospective experience was included.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation